Animal models for cystic fibrosis: a systematic search and mapping review of the literature. Part 2: nongenetic models. (August 2021) - Leenaars, Cathalijn HC; Vries, Rob BM de; Reijmer, Joey; Holthaus, David; Visser, Damian; Heming, Anna; Elzinga, Janneke; Kempkes, Rosalie WM; Beumer, Wouter; Punt, Carine; Meijboom, Franck LB; Ritskes-Hoitinga, Merel
Various animal models are available to study cystic fibrosis (CF). These models may help to enhance our understanding of the pathology and contribute to the development of new treatments. We systematically searched all publications on CF animal models. Because of the large number of models retrieved, we split this mapping review into two parts. Previously, we presented the genetic CF animal models. In this paper we present the nongenetic CF animal models. While genetic animal models may, in theory, be preferable for genetic diseases, the phenotype of a genetic model does not automatically resemble human disease. Depending on the research question, other animal models may thus be more informative. We searched Pubmed and Embase and identified 12, 303 unique publications (after duplicate removal). All references were screened for inclusion by two independent reviewers. The genetic animal models for CF (from 636 publications) were previously described. The non-genetic CF models (from 189 publications) are described in this paper, grouped by model type: infection-based, pharmacological, administration of human materials, xenografts and other. As before for the genetic models, an overview of basic model characteristics and outcome measures is provided. This CF animal model overview can be the basis for an objective, evidence-based model choice for specific research questions. Besides, it can help to retrieve relevant background literature on outcome measures of interest.